2020
DOI: 10.30589/pgr.v4i1.169
|View full text |Cite
|
Sign up to set email alerts
|

Governing Village Fund in Indonesia: Is It Erradicating Poverty?

Abstract: This study was conducted by inding that there were inconsistencies and uncorrelated data from the government score-based report about Village Fund, and the public perception of the village fund. This research observes relevance of numbers using the Impact Assessment concepts. This research can act as a useful insight for the governments, researchers and societies to evaluate the commitment of the government to build Indonesia from village. By using descriptive quantitative research method, this paper criticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
9
0
4
Order By: Relevance
“…In contrast to studies of institutional approaches, studies with a political economy approach can explain and confirm that the problem of poverty is inseparable from the problem of inequality in power relations in the social structure of society that is formed in rural areas [17]. The results show that the development of village physical infrastructure only benefits a handful of people [18] and causes social ICMEd inequality to widen [19]. Thus, discussing social inequality is very important to see the impact of Village Fund assistance on the poor during the current Covid-19 pandemic.…”
Section: Related Work/literature Reviewmentioning
confidence: 99%
“…In contrast to studies of institutional approaches, studies with a political economy approach can explain and confirm that the problem of poverty is inseparable from the problem of inequality in power relations in the social structure of society that is formed in rural areas [17]. The results show that the development of village physical infrastructure only benefits a handful of people [18] and causes social ICMEd inequality to widen [19]. Thus, discussing social inequality is very important to see the impact of Village Fund assistance on the poor during the current Covid-19 pandemic.…”
Section: Related Work/literature Reviewmentioning
confidence: 99%
“…This is a result of the development of too much focus on the physical infrastructure of the village. Physical development in the village was carried out, but human development such as health, education, and improvement of basic skills was not carried out so that national problems such as stunting and maternal mortality/MMR were not overcome [12] in his research, it was concluded that Village Funds caused an increase in infrastructure and community empowerment programs, but Village Funds still had problems in its distribution and utilization so that Village Funds was not related to poverty reduction. A study conducted by [13] shows that the transfer of Village Funds is not significant in overcoming the problem of income inequality.…”
Section: Production and Incomementioning
confidence: 99%
“…Terdapat ketimpangan dalam besaran dana yang diterima dengan jumlah penduduk miskin; daerah dengan jumlah penduduk miskin yang rendah namun memiliki jumlah desa yang banyak akan memperoleh alokasi dana desa yang jauh lebih besar dari daerah dengan jumlah penduduk miskin tinggi namun jumlah desanya relatif sedikit (KOMPAK, 2017). Kebijakan Dana Desa juga dinilai belum efektif dalam mendorong pengentasan kemiskinan desa (Imawan & Purwanto, 2020) dan membuka lapangan kerja (Arifin dkk, 2020). Dalam konstruksi formula alokasi saat ini, komponen insentif yang berfungsi mendorong peningkatan kinerja tata kelola pemerintahan desa memiliki bobot yang lebih rendah dari komponen afirmasi yang lebih bersifat pemerataan.…”
Section: Pendahuluanunclassified